Cultural Bridges: The Role of African American Intellectuals in the Harlem Renaissance and Their Influence on Pan-Africanism and African Decolonization - EWALEFOH, Ernest (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
This research, situated within the field of Cultural Heritage Studies, explores the role of African American intellectuals during the Harlem Renaissance and their influence on Pan-Africanist movements and decolonization efforts in Africa. Using a qualitative research methodology, the study analyzes historical texts, primary sources, and scholarly works to examine how figures like W.E.B. Du Bois and Marcus Garvey connected the struggles of African Americans with anti-colonial movements in Africa. The Harlem Renaissance, a cultural and intellectual movement, served as a platform for African American intellectuals to redefine Black identity and promote racial pride, while also influencing African leaders through cross-continental dialogue. The research highlights the interconnectedness of African and African American struggles, demonstrating how the Harlem Renaissance contributed to the decolonization of Africa and the global fight against racial oppression. By focusing on the intellectual and cultural exchanges between the African diaspora and the African continent, this study underscores the transformative power of cultural heritage in shaping political and social movements. The importance of this research lies in its contribution to understanding the global dimensions of the Harlem Renaissance and Pan-Africanism, offering insights into how cultural and intellectual movements can drive historical change. It also emphasizes the significance of African American intellectuals in shaping decolonization efforts, challenging Eurocentric narratives, and fostering a sense of unity among people of African descent. This study is significant for scholars in Cultural Heritage Studies, African American studies, and decolonization studies, as it provides a nuanced perspective on the role of cultural heritage in global liberation movements.